Analisis Sistem Akuntansi Penagihan Gaji/Upah Pada Perusahaan Outsourcing/Alih Daya - Oktaviani Nur Fadilah; Amin Sadiqin (CV ODIS, 2022)
PT. Prima Makmur Bersama or commonly called PT. PMB is an outsourcing company that is a service company engaged in the provision of labor. Until now PT. PMB has more than 20 partners throughout Indonesia and employs hundreds of contract employees under its auspices. Discussing employees will not be separated from the name of salary/wages. Companies/businesses are obliged to issue salaries/wages for their employees. Salary/wages themselves are used in return for services for work that has been done during a certain period. Every month the company is obliged to pay the employee's salary/wage, where the employee's salary transfer company will be billed to each partner in accordance with the salary period and the location of the employee is placed. This certainly requires an effective and efficient flow/salary billing process, so that the billing process is smooth, fast, and precise. Therefore, in this article, the author wants to discuss the flow of employee salary billing to partners/users in the outsourcing company. The data collection carried out is a direct observation of the parties concerned.